Transient Stability Analysis of Photovoltaic System with Experimental Shading Effects - Saidi, A. S.; Ben Slimene, M.; Khlifi, M. A. (Engineering, Technology & Applied Science Research, 2018)
This paper presents the transient stability analysis of a photovoltaic (PV) system with account shading effects. Voltage and transient stability effect of PV system are assessed functions of an experimental study. The current advances in shading effect and temperature control of PV panels are studied. The study is performed on modeling and simulation of PV system with account shading effect. A shading effect system is introduced to reflect the transient response characteristics of PV generation model. An experimental setup is designed, constructed and assembled. The setup is provided with the necessary measuring instruments to carry out the required tests. A perspective on the other shading techniques for PV panels will be discussed in this paper.